Mucosal immune cell populations and the bacteriome of adenoids and tonsils from people living with HIV on suppressive antiretroviral therapy - Briceño, Olivia; Gónzalez-Navarro, Mauricio; Montufar, Nadia; Chávez-Torres, Monserrat; Abato, Indira; Espinosa-Sosa, Ariana; Ablanedo-Terrazas, Yuria; Luna-Villalobos, Yara; Ávila-Ríos, Santiago; Reyes-Terán, Gustavo; Pinto-Cardoso, Sandra (Frontiers in Microbiology, 2022)
Ear, nose, and throat (ENT) conditions are prevalent in people living with HIV (PLWH) and occur at all strata of CD4 counts and despite antiretroviral therapy (ART). ENT conditions are underreported in PLWH. Also, little is known about the adenotonsillar microbiota and its relation to resident adaptive and innate immune cells. To bridge this gap, we characterized immune cell populations and the bacterial microbiota of two anatomical sites (adenoids, tonsils) and the oral cavity. Adenoids and tonsils were obtained from PLWH (n = 23) and HIV-seronegative individuals (SN, n = 16) after nasal surgery and tonsillectomy and processed for flow cytometry. Nasopharyngeal, oropharyngeal swabs, and oral rinses were collected prior to surgery for 16S sequencing. Wilcoxon rank sum test, principal coordinate analysis, permutational multivariate analysis of variance, and linear discriminant analysis (LEfSe) were used to assess differences between PLWH and SN. Spearman’s correlations were performed to explore interactions between the bacteriome and mucosal immune cells. Of the 39 individuals included, 30 (77%) were men; the median age was 32 years. All PLWH were on ART, with a median CD4 of 723 cells. ENT conditions were classified as inflammatory or obstructive, with no differences observed between PLWH and SN. PLWH had higher frequencies of activated CD4+ and CD8+ T cells, increased T helper (Th)1 and decreased Th2 cells; no differences were observed for B cells and innate immune cells. Alpha diversity was comparable between PLWH and SN at all 3 anatomical sites (adenoids, tonsils, and oral cavity). The impact of HIV infection on the bacterial community structure at each site, as determined by Permutational multivariate analysis of variance, was minor and not significant. Two discriminant genera were identified in adenoids using LEfSe: Staphylococcus for PLWH and Corynebacterium for SN. No discriminant genera were identified in the oropharynx and oral cavity. Niche-specific differences in microbial diversity and communities were observed. PLWH shared less of a core microbiota than SN. In the oropharynx, correlation analysis revealed that Th17 cells were inversely correlated with bacterial richness and diversity, Filifactor, Actinomyces and Treponema; and positively correlated with Streptococcus. Our study contributes toward understanding the role of the adenotonsillar microbiota in the pathophysiology of ENT conditions.